Image Processing For Identification of Breast Cancer: A Literature Survey - Arokiyamary Delphina, A.; Kamarasan, M.; S. Sathiamoorthy (Asian Journal of Electrical Sciences, 2018)
Breast cancer has become the leading cause of cancer deaths among women. To decrease the related mortality, disease must be treated as early as possible, but it is hard to detect and diagnose tumors at an early stage. Manual attempt have proven to be time consuming and inefficient in many cases. Hence there is a need for efficient methods that diagnoses the cancerous cell without human involvement with high accuracy. Mammography is a special case of CT scan who adopts X-ray method & uses the high resolution film so that it can detect well the tumors in the breast. This paper reviews on the detection of the breast cancer by image processing techniques.